2004
DOI: 10.1074/jbc.m400457200
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatitis E Virus Open Reading Frame 3 Protein Activates ERK through Binding and Inhibition of the MAPK Phosphatase

Abstract: The hepatitis E virus causes acute viral hepatitis endemic in much of the developing world and is a serious public health problem. However, due to the lack of an in vitro culture system or a small animal model, its biology and pathogenesis are poorly understood. We have shown earlier that the ORF3 protein (pORF3) of hepatitis E virus activates ERK, a member of the MAPK superfamily. Here we have explored the mechanism of pORF3-mediated ERK activation and demonstrated it to be independent of the Raf/MEK pathway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 69 publications
2
87
0
Order By: Relevance
“…This suggests that there may be further, as yet unidentified, ways in which NS5A and/or other nonstructural proteins are able to modulate the Ras-ERK pathway. In this regard, the hepatitis E virus ORF3 protein was recently shown to activate ERK by inactivating an ERK-specific phosphatase (Kar-Roy et al, 2004). It is intriguing to speculate that, as in the case of the EGFR and receptor-proximal events in the EGFR signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there may be further, as yet unidentified, ways in which NS5A and/or other nonstructural proteins are able to modulate the Ras-ERK pathway. In this regard, the hepatitis E virus ORF3 protein was recently shown to activate ERK by inactivating an ERK-specific phosphatase (Kar-Roy et al, 2004). It is intriguing to speculate that, as in the case of the EGFR and receptor-proximal events in the EGFR signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ORF3, mapped between ORF1 and ORF2, encodes a 13.5-kDa protein that is associated with the membrane as well as with the cytoskeleton fraction (27). This protein is shown to be phosphorylated by the cellular mitogen-activated protein kinase (6,8). The ORF3 protein may have a regulatory function (6,8).…”
Section: Hepatitis E Virus (Hev) Is a Noncultivable Virus That Causesmentioning
confidence: 99%
“…This protein is shown to be phosphorylated by the cellular mitogen-activated protein kinase (6,8). The ORF3 protein may have a regulatory function (6,8). Ever since HEV was first discovered in 1980 and visualized by immune electron microscopy in 1983 (2), many efforts have been made, using different expression systems, to express the structural protein (5,11,17,26).…”
Section: Hepatitis E Virus (Hev) Is a Noncultivable Virus That Causesmentioning
confidence: 99%
“…The exact functions of vp13 in HEV infection remain unknown although the findings of a number of studies have shown that it plays a role in cellular signaling pathways (13,17,24,(34)(35)(36)40). During subcellular fractionation of COS-7 cells transfected with a vp13-expressing plasmid, vp13 was found to partition with the cytoskeletal fraction (40).…”
Section: Hepatitis E Virus (Hev) Is the Causative Agent Of Hepatitis mentioning
confidence: 99%